Hydrocarbon generation, expulsion, and retention characteristics of the Permian Fengcheng shale and Lucaogou shale in the Junggar Basin: implications for the exploration of lacustrine shale oil - He, Wenjun; Li, Zhiming; Li, Changrong; He, Jinyi; Leng, Junying; Sun, Zhongliang; Liu, Deguang; Yang, Sen (Frontiers in Earth Science, 2025)
Hydrocarbon generation patterns are crucial for defining favorable exploration maturity intervals and targets for shale oil. The Permian Fengcheng shale and Lucaogou shale in the Junggar Basin, as significant targets for shale oil exploration, study on their hydrocarbon generation, expulsion, and retention characteristics are insufficient. This study establishes hydrocarbon generation patterns for the Fengcheng shale and Lucaogou shale using a semi-open thermal simulation system, combined with rock pyrolysis, vitrinite reflectance (Ro), total organic carbon (TOC) analysis, carbon isotope analysis, gas chromatography-mass spectrometry (GC-MS), mercury porosimetry, and nitrogen adsorption. Additionally, a multivariate regression model was employed to systematically evaluate the primary controlling factors of hydrocarbon expulsion ratio. Based on these results, favorable exploration maturity intervals and targets for the Fengcheng shale and Lucaogou shale were identified. The results indicate that the hydrocarbon generation potential of Fengcheng shale was superior to that of Lucaogou shale, whether considering gas yield or oil yield. However, Lucaogou shale began the thermal degradation earlier than Fengcheng shale and has a broader degradation window. The corresponding (TR) is slightly higher for Fengcheng shale. The Lucaogou shale exhibited significantly higher hydrocarbon expulsion ratios compared to Fengcheng shale, with a maximum hydrocarbon expulsion ratio 2.1 times that of Fengcheng shale. Mesopore volume and its connectivity were critical factors affecting the hydrocarbon expulsion ratio, whereas oil mobility and macropore volume have relatively limited effects. The optimal maturity interval for shale oil exploration as Ro = 1.0%–1.1% for the Fengcheng shale and Ro = 0.9%–1.1% for the Lucaogou shale. Exploration of the Fengcheng shale should focus on lithofacies assemblages, the dolomitic mixed rock-shale assemblages in the shore-shallow lake facies represent the primary exploration target. Exploration of the Lucaogou shale should focus on source-reservoir assemblages, with a higher reservoir-to-shale thickness ratio being the primary exploration target. These findings provide support for the exploration and development decisions of shale oil in the Junggar Basin.